2007
DOI: 10.1152/ajpgi.00145.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia causes hepatitis in a mouse model of diet-induced fatty liver

Abstract: Obstructive sleep apnea (OSA) causes chronic intermittent hypoxia (CIH) during sleep. OSA is associated with nonalcoholic steatohepatitis (NASH) in obese individuals and may contribute to progression of nonalcoholic fatty liver disease from steatosis to NASH. The purpose of this study was to examine whether CIH induces inflammatory changes in the liver in mice with diet-induced hepatic steatosis. C57BL/6J mice (n = 8) on a high-fat, high-cholesterol diet were exposed to CIH for 6 mo and were compared with mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
179
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 66 publications
6
179
0
Order By: Relevance
“…Our previous experiments in the mouse model showed that CIH increases lipid peroxidation and activates a redox-dependent transcription factor, NF-kB, in the liver (44,45). We have also shown that, in mice with diet-induced hepatic steatosis, but not in mice with normal livers, CIH increases liver levels of proinflammatory cytokines IL-1b, IL-6, macrophage inflammatory protein-2, and tumor necrosis factor-a as well as a1(I) collagen and indices of lobular inflammation and fibrosis (27,45,46). Our present report and previous experimental data suggest that the hypoxic stress of OSA may induce oxidative stress in the livers of patients with severe obesity, leading to inflammation and fibrosis, which culminate in NASH.…”
Section: Osa and Nash In Severe Obesitymentioning
confidence: 69%
See 2 more Smart Citations
“…Our previous experiments in the mouse model showed that CIH increases lipid peroxidation and activates a redox-dependent transcription factor, NF-kB, in the liver (44,45). We have also shown that, in mice with diet-induced hepatic steatosis, but not in mice with normal livers, CIH increases liver levels of proinflammatory cytokines IL-1b, IL-6, macrophage inflammatory protein-2, and tumor necrosis factor-a as well as a1(I) collagen and indices of lobular inflammation and fibrosis (27,45,46). Our present report and previous experimental data suggest that the hypoxic stress of OSA may induce oxidative stress in the livers of patients with severe obesity, leading to inflammation and fibrosis, which culminate in NASH.…”
Section: Osa and Nash In Severe Obesitymentioning
confidence: 69%
“…The ''second hit'' induces progression of hepatic steatosis to NASH (21). Obesity, age over 45 years, diabetes, hypertriglyceridemia, and hypertension have been identified as risk factors for the progression of NAFLD (24), but causes for NAFLD progression, which occurs in approximately 25-30% of patients with hepatic steatosis, remain unknown (25).We have previously used a mouse model of CIH and have shown that CIH induces insulin resistance in genetically obese mice and converts diet-induced hepatic steatosis to NASH (26,27). Although obesity and OSA have been implicated in the development of systemic inflammation, insulin resistance, and NAFLD (2-4, 10-21, 24, 28), the inflammatory, metabolic, and hepatic profiles of severe obesity with and without concomitant sleep apnea have not been elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known about this interaction [49,50]. Hypoxia induces oxidative stress in the brain [51,52] and is associated with increased levels of proinflammatory cytokines, such as TNF-α in pig [53], in humans [54] and in mice [55]. Indeed, the levels of TNF-α may remain elevated in the affected brain tissue for at least 24 h after an ischemic insult [16,56] and TNF-α itself causes oxidative stress in the brain [57].…”
Section: Tnf-α and Hypoxia In The Cnsmentioning
confidence: 99%
“…67 Still in the absence of obesity, chronic intermittent hypoxia leads to mild elevated levels of liver enzymes, 68 liver injury by oxidative stress and excessive glycogen accumulation in hepatocytes and sensitizes the liver for a second injury. 69 It seems that sleep apnea is the leading cause of adverse metabolic outcomes. Although, further research need to conclude whether a cause and effect relationship exist.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%